2021
DOI: 10.1523/jneurosci.1980-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Status Alters Alzheimer's Disease Progression through NLRP3-Dependent Inflammation

Abstract: Alzheimer's disease is a devastating neurodegenerative disease with a dramatically increasing prevalence and no disease-modifying treatment. Inflammatory lifestyle factors increase the risk of developing Alzheimer's disease. Zinc deficiency is the most prevalent malnutrition in the world and may be a risk factor for Alzheimer's disease potentially through enhanced inflammation, although evidence for this is limited. Here we provide epidemiological evidence suggesting that zinc supplementation was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Decreased bioavailability of Zn and may lead to NLRP3-driven inflammation. This is also evident in Alzheimer's diseases and leads to cognitive decline in animal models, which may translate to ASD models (Pellegrini et al, 2020;Rivers-Auty et al, 2021). Increased cytokine expression and the activation of glial cells have been linked to synapse loss and modification of synaptic function (Kim et al, 2020).…”
Section: Inflammasomicsmentioning
confidence: 99%
“…Decreased bioavailability of Zn and may lead to NLRP3-driven inflammation. This is also evident in Alzheimer's diseases and leads to cognitive decline in animal models, which may translate to ASD models (Pellegrini et al, 2020;Rivers-Auty et al, 2021). Increased cytokine expression and the activation of glial cells have been linked to synapse loss and modification of synaptic function (Kim et al, 2020).…”
Section: Inflammasomicsmentioning
confidence: 99%
“…In addition to affecting synaptic function, zinc has been shown linked with oxidative stress as well as neuroin ammation that are important in AD disease development [11]. In the present study, pretreatment of SH-SY5Y cells by emodin suppressed the zinc-induced ROS generation, reduced the formation of lipid peroxidation product (4-HNE), and decreased the level of DNA damage marker (8-OHdG).…”
Section: Discussionmentioning
confidence: 52%
“…The synergistic interaction between Zn 2+ and reactive oxygen species (ROS) has been shown to amplify the ischemic brain injury in rodent model [9] through direct ROS generation or through, mitochondrial Ca 2+ uniporter [10]. Recent study indicates that zinc status introduce through In ammation through NLRP3-mediated pathway [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been long known that trace metals, such as zinc, are impacting on protein aggregation, synaptic signaling, mitochondrial function, oxidative stress and inflammation, ultimately resulting in synapse dysfunction and neuronal loss in the AD brain. 61 It was shown that zinc status alters AD progression through NLRP3-dependent inflammation, 62 and zinc dyshomeostasis has been reported in the plasma of AD patients. 63 Another intriguing finding was the very significant contribution of helix-loop-helix transcription factors to the dysregulated redox gene expression pattern.…”
Section: Discussionmentioning
confidence: 99%